Influence of epiretinal membrane on the measurement of peripapillary retinal nerve fibre layer thickness using spectral-domain coherence tomography. Issue 8 (5th November 2015) - Lee, Yun Ha; Bae, Hyoung Won; Seo, Sang Jin; Lee, Sang Yeop; Beon, Seok Ho; Kang, Sungyong; Kim, Chan Yun
Abstract : Background/aims: To investigate the effect of epiretinal membrane (ERM) on peripapillary retinal nerve fibre layer (RNFL) thickness measurements using spectral-domain optical coherence tomography (Spectralis; Heidelberg Engineering). Methods: A total of 134 patients with idiopathic ERM and 63 healthy controls were included in this observational comparative study. We categorised ERMs into three severity grades, based on retinal appearance in macular scans. All eyes with ERM were classified into two groups; those involving the peripapillary scan area (ERM+pp, n=68 eyes) and not involving the peripapillary scan area (ERM−pp, n=66 eyes) using the macular disc scan. Peripapillary RNFL thickness was compared between related subgroups as (ERM+pp) or (ERM−pp) group. Results: Temporal peripapillary RNFL thickness was significantly greater in the ERM+pp group (109.44±22.91 μm), followed by the ERM−pp (82.60±11.77 μm, p<0.001) and control (75.42±10.49 μm, p<0.001) groups. Temporal peripapillary RNFL thickness significantly increased with ERM grade in the ERM+pp and ERM−pp groups (both p<0.001). The peripapillary RNFL thickness was overestimated (exceeded 99th percentile) in the temporal sector in 49 eyes (72.1%) in the ERM+pp group and in 5 eyes (7.6%) in the ERM−pp group. Conclusions: Temporal and global peripapillary RNFL thickness is significantly higher in eyes with ERM, especially when the ERM extends into the peripapillary area. However, some eyes with an ERM that does not involve the peripapillary scan area still show peripapillary RNFL thickening. Measured peripapillary RNFL thickness was significantly and positively correlated with ERM severity.